Efektifitas Aromaterapi Lemon Dan Terapi Musik Lullaby Terhadap Nyeri Pasca Operasi Sectio Caesarea - Maya Novita Sari; Irma Herliana; Saiful Gunardi (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Post SC patients will complain of pain in the incision area caused by tearing tissue in the abdominal wall and uterine wall. Back pain or pain in the nape is also a complaint commonly felt by post-SC mothers, it is due to the effects of using epidural anesthesia during surgery. But after the operation is complete and the patient begins to regain consciousness, he will feel pain in the part of the body that undergoes surgery. Sectio caesarea surgery has complications of infection, bleeding, injury to the bladder, The purpose of this study was to determine the Comparison of the Effectiveness of aroma therapy lemon and classical music therapy lullaby Against the Pain Scale in Post Partum Mothers after sectio caesarea surgery in the Babusalam Room of Tugu Ibu Hospital in 2023. Research Design Quasi-experimental method is a research method that in its implementation does not use random assignment (random assignment) but by using existing groups. The population in this study is all postoperative caesarean section patients totaling 150 people from caesarean section data from April to May 2023 at Tugu Ibu Hospital. The sample in this study was 30 people divided into 2 intervention groups, each group consisting of 15 people. This study obtained data that before being given therapy, a comparison of post-test pain in the lemon aromatherapy group and lullaby classical music after caesarean section surgery obtained a p value of 0.000, because p > 0.05 it was concluded that there was a significant difference in pain scale after being given lemon aromatherapy therapy and lullaby classical music, which was more effective lemon aroma therapy. Advice For health workers or nurses can apply the administration of Aroma Therapy and Classical Music Therapy to reduce the Pain Scale in Post Partum Mothers after sectio caesarea surgery